Colonic tuberculosis: a case report - Ghada Gharbi; Moufida Mahmoudi; Manel Yakoubi; Asma Ben Mohamed; Amal Khsiba; Mohamed Karim M'Farrej; Mahdi Bouassida; Emna Chelbi; Lamine Hamzaoui (Future Science OA, 2022)
Aim: Colonic tuberculosis is rare. It accounts for 2–3% of abdominal tuberculosis. Clinical, radiological and endoscopic features are nonspecific. The diagnosis must be considered in front of chronic abdominal pain, vesperal fever and weight loss with on colonoscopy the presence of nodules or ulcers. The diagnosis is made on pathological findings. Case report: We report a case of an 82-year-old female patient with the diagnosis of colonic tuberculosis. The diagnosis were suspected on clinical presentation: chronic abdominal pain, fever and weight loss. The colonoscopy showed a nodular aspect of the left and sigmoid colonic mucosa and the pathology examination of the multiple biopsy specimens showed an epithelioid and gigantocellular granulomas with caseous necrosis. Conclusion: In front of a nonspecific clinical and endoscopic aspects, multiples colonic biopsies are mandatory to rule out differential diagnosis and confirm colonic tuberculosis.